2015
DOI: 10.11648/j.ijepp.20150305.14
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fertility Status and Productivity Trends Along a Toposequence: A Case of Gilgel Gibe Catchment in Nadda Assendabo Watershed, Southwest Ethiopia

Abstract: The Impact of landscape positions and land use type on properties as well as land productivity are commonly observed in Ethiopia. The study was therefore conducted to quantify soil fertility and productivity trends under three land uses along the gradient (lower, middle and upper slope positions) of Nadda Assendabo watershed, Southwest Ethiopia. Thus field survey was covered a total of 54 composite soil samples using split plots (for soil physical properties) and split-split factorial arrangements with randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
2
8
2
Order By: Relevance
“…Correspondingly, the data showed that the minimum value of PSB (31.69%) was obtained from strongly sloping and the maximum value of PBS (40.95%) was obtained from moderately steep slope (Table 2). This result disagrees with findings of Mulugeta (2015) and Siraj et al, (2015) reported that PBS was affected by slope positions.…”
Section: Percentage Of Base Saturationcontrasting
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, the data showed that the minimum value of PSB (31.69%) was obtained from strongly sloping and the maximum value of PBS (40.95%) was obtained from moderately steep slope (Table 2). This result disagrees with findings of Mulugeta (2015) and Siraj et al, (2015) reported that PBS was affected by slope positions.…”
Section: Percentage Of Base Saturationcontrasting
confidence: 99%
“…According to Likassa (2014) reported the shade trees were more environmental sound as compared to chemical fertilization is added to soil. On the other hand, according to Siraj et al, (2015), Mulugeta (2015) and Fanuel et al, (2016), who, revealed that exchangeable potassium was significantly influenced by the slope gradient classes, which were opposite to the present study. Similarly, Mulugeta (2015) reported that the accumulation of exchangeable magnesium contents were relatively higher on lower slope gradient over medium slope and upper slope gradients, respectively.…”
Section: Exchangeable Potassiumcontrasting
confidence: 93%
See 1 more Smart Citation
“…39 Most of the soil nutrients significantly decreased due to soil erosion and landscape features with increasing slope steepness and unwise utilization of land. 40 The deposition of sediment on the lower slope has had a noticeable effect on the soil's physical and chemical properties. 41 Soil bunds reduce runoff, as well as soil and nutrient losses and organic carbon loss from cultivated lands.…”
Section: Status Of Soil Chemical Properties At Different Terrace Positionsmentioning
confidence: 99%
“…However, soil nutrient removal, organic matter depletion, and soil erosion are seriously threatening the sustainability of agricultural production in Ethiopia [6,7]. e shortage of land in densely populated areas of the country, to meet the demand for food production, led to conversion of vast tracts of forestlands into cultivated crop lands [8].…”
Section: Introductionmentioning
confidence: 99%